Interface between chemical exposure and risks to children’s health: Nursing undergraduate students' knowledge (Research, Society and Development, 2021)
Introduction: The advances in prevention politics and research on children's environmental health require the qualification of health professionals with knowledge and skills on the effects and risks of exposure of environmental chemical contaminants to children's health. Objective: Evaluate if nursing students were able to identify the relationship between the chemical exposure and the risks to children’s health and if this knowledge is different based on each year of college. Method: Cross-sectional study with a questionnaire applied to 120 Nursing undergraduate students, from Federal Fluminense University, Rio das Ostras campus, Rio de Janeiro, Brazil. Statistical analysis involved the Chi-square test, Fisher’s exact test, and Kruskal-Wallis test. Results: There was a significant difference in the students' knowledge among the undergraduate years about the effect of chemical exposure during breastfeeding, drug use during pregnancy, and exposure to soil with pesticides during childhood. The cohort with the highest comprehension of these effects was third-year students (in a five-year program. Not only the knowledge about methylmercury was different throughout the five years of the nursing course, but 44.9% weren’t able to answer about this xenobiotic. Conclusion: Participants evaluated in their final year of study were unable to demonstrate appropriate knowledge of some factors of chemical exposure in children, which indicates that education on this theme insufficient. These results highlight the fundamental need for improvements in teaching related to children's environmental health, especially toxicology, in the nursing curriculum.